Transcriptomic profiling of skeletal muscle adaptations to exercise and inactivity - Nicolas J. Pillon (Nature Portfolio, 2020)
The pathways that underlie the effects of exercise on metabolism remain incompletely described. Here, the authors perform a meta-analysis of transcriptomic data from 66 published datasets of human skeletal muscle. They identify pathways selectively activated by inactivity, aerobic or resistance exercise, and characterize NR4A3 as one of the genes responsive to inactivity.